Alterações histopatológicas em miocárdio de cães com parvovirose - Magalhães, Aline Oliveira Coelho (2008)
Parvoviruses is a viral disease characterized by an acute hemorrhagic gastroenteritis, caused by a canine parvovirus (CPV) that is stable in the environment, able to bear pH variations and high temperatures. It is resistant to many common disinfectants and can survive for many months in contaminated areas. There are two common clinical forms of the disease: the myocardial and the gastroenteric. This work had as objective to analyse microscopically the cardiopathy cases, diagnosticated macroscopically during the necropsy of dogs with parvovirus detected in faeces. In the 100 samples send to the Histopathology Laboratory, from the University of Uberaba, they get in the left ventricular myocardium the following alterations: myocarditis 38%, hemorrhage 43%, hyaline degeneration 21% and hyperemia 79%. Having been carried out the Qui-Quadrado test with a significance level of 0,05, we can conclude that there is association (p = 0,02) between the infected animals with the parvoviruses virus and the histopathologyc alterations observed in the left ventricular myocardium.